Human tumor necrosis factor alpha gene regulation by virus and lipopolysaccharide. - Goldfeld, A E (1990)
We have identified a region of the human tumor necrosis factor alpha (TNF-alpha) gene promoter that is necessary for maximal constitutive, virus-induced, and lipopolysaccharide (LPS)-induced transcription. This region contains three sites that match an NF-kappa B binding-site consensus sequence. We show that these three sites specifically bind NF-kappa B in vitro, yet each of these sites can be deleted from the TNF-alpha promoter with little effect on the induction of the gene by virus or LPS. Moreover, when multimers of these three sites are placed upstream from a truncated TNF-alpha promoter, or a heterologous promoter, an increase in the basal level of transcription is observed that is influenced by sequence context and cell type. However, these multimers are not sufficient for virus or LPS induction of either promoter. Thus, unlike other virus- and LPS-inducible promoters that contain NF-kappa B binding sites, these sites from the TNF-alpha promoter are neither required nor sufficient for virus or LPS induction. Comparison of the sequence requirements of virus induction of the human TNF-alpha gene in mouse L929 and P388D1 cells reveals significant differences, indicating that the sequence requirements for virus induction of the gene are cell type-specific. However, the sequences required for virus and LPS induction of the gene in a single cell type, P388D1, overlap.